Os cuidados com pacientes fora de recursos terapêuticos de cura: uma análise das práticas discursivas de alunos do curso de enfermagem sobre a morte - Walter, Luciene Carneiro (2017)
The significant increase in life expectancy is not accompanied, necessarily, by the quality of the same. Even if this increase continues to progress, death is inevitable. Biotechnological advances are of paramount importance, indisputably; but with the advent of equipment that prolongs life, and in cases of chronic-degenerative diseases, when curative care is no longer effective, we institutionalize the process of dying and the sick person experiences it in life and, in the vast majority of cases, with suffering and pain. The (re)humanization in the treatment of patients out of therapeutic possibilities of cure is an urgent social demand, since humanization in health care has been delegated to a distant plan. The objective of this work was to understand the discursive practices of first year students of a nursing course in Curitiba/PR related to the humanization of the care of patients out of therapeutic possibilities of cure and in the process of dying. For that, discussion groups were held in four meetings with six first-year nursing students. The analysis was performed through discourse analysis. It was observed that, throughout the meetings, three axes manifested themselves in the discursive practices of the group: the medical hierarchy x nursing; the nursing hierarchy x patient; and the imposition of religious faith. Faced with a patient out of therapeutic possibilities of cure, the act of caring for the nursing professional would legitimize what is best for the patient and his family; And for students, the patient with the diagnosis of chronic degenerative disease, with a prognosis of death, should always maintain hope in a miracle.